2020
DOI: 10.3390/molecules25153531
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Metabolites from Grapes and Red Wine in Breast Cancer Chemoprevention and Therapy

Abstract: Phytochemicals and their metabolites are not considered essential nutrients in humans, although an increasing number of well-conducted studies are linking their higher intake with a lower incidence of non-communicable diseases, including cancer. This review summarizes the current findings concerning the molecular mechanisms of bioactive compounds from grapes and red wine and their metabolites on breast cancer—the most commonly occurring cancer in women—chemoprevention and treatment. Flavonoid compounds like fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 237 publications
(290 reference statements)
0
14
0
Order By: Relevance
“…Rapid absorption, poor bioavailability, and low aqueous solubility are some of the crucial limitations and challenges of the in vivo use of resveratrol [12,13]. Therefore, different methodological approaches, such as solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs), have been used to improve the poor aqueous solubility and the low bioavailability of resveratrol [14].…”
Section: Absorption and Metabolism Of Resveratrolmentioning
confidence: 99%
“…Rapid absorption, poor bioavailability, and low aqueous solubility are some of the crucial limitations and challenges of the in vivo use of resveratrol [12,13]. Therefore, different methodological approaches, such as solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs), have been used to improve the poor aqueous solubility and the low bioavailability of resveratrol [14].…”
Section: Absorption and Metabolism Of Resveratrolmentioning
confidence: 99%
“…A moderate amount of alcohol from wine consumption (150-300 mL/day) can protect against cardiovascular disease, dietary cancers, ischemic stroke, diabetes, hypertension and so on [50]. Additionally, the polyphenols from wine have antioxidant, antiviral, antibacterial and anti-carcinogen proprieties which imply health benefits [50][51][52][53]. Apart this, vine and wine has an important economic status, including in the world trade market as well as the agro-tourism to wineries and wine-growing areas.…”
Section: Introductionmentioning
confidence: 99%
“…A correct and complete understanding of phytochemical compositions and antimicrobial activities of different anatomical parts of grapes from Vitis vinifera L., as well as differences resulted from the variety and/or the culture management system, may lead to developing new applications, much more specific, from a wide spectrum already known. Thus, recent studies [19,40,[66][67][68][69] have shown a direct relationship between the therapeutic benefit, chemo-preventive effects (anticancer) and the red grapes consumption, in various forms. The role of the bioactive compounds (e.g., proanthocyanidins, anthocyanins and other flavonoids, hydroxycinnamates, and stilbenes such as resveratrol) has been investigated, and antioxidant, antimicrobial, antitumor effects have been found, as well as anti-inflammatory properties, and inhibiting lipid peroxidation.…”
Section: Grapes As Functional Foodsmentioning
confidence: 99%